1983
DOI: 10.1007/bf00990222
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two components of the sex pheromone of the moth,Epiphyas postvittana (Lepidoptera, Tortricidae)

Abstract: Two compounds, (E)-11-tetradecen-1-yl acetate and (E,E)-9,11-tetradecadien-1-yl acetate, have been identified in extracts of females of the lightbrown apple moth,Epiphyas postvittana (Walker). The two compounds are active as a coalitive pair and are present in extracts of females in a ratio of about 20∶1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…Individual males were released into the tunnel between the second and fourth hours of the scotophase according to previously outlined procedures (Muggleston & Foster 1989). In all the experiments, the pheromone source was a red rubber septum (Thomas Scientific Inc., Philadelphia) on which had been absorbed the appropriate amounts of (E)-l 1-tetradecenyl acetate (El l-14:OAc; Sigma Chemical Company, St Louis, Missouri; >99% isomerically pure as determined by capillary gas chromatography) and (E,E)-9,ll-tetradecadienyl acetate (E,E-9,ll-14:OAc, gift from Shin Etsu Chemical Co. Ltd, Tokyo, Japan; approximately 94% isomerically pure) in a ratio of 100:5 (Bellas et al 1983) dissolved in 25 \x\ of n-pentane. When not in use, the pheromone sources were stored at -15°C.…”
Section: Wind Tunnel Protocolmentioning
confidence: 99%
“…Individual males were released into the tunnel between the second and fourth hours of the scotophase according to previously outlined procedures (Muggleston & Foster 1989). In all the experiments, the pheromone source was a red rubber septum (Thomas Scientific Inc., Philadelphia) on which had been absorbed the appropriate amounts of (E)-l 1-tetradecenyl acetate (El l-14:OAc; Sigma Chemical Company, St Louis, Missouri; >99% isomerically pure as determined by capillary gas chromatography) and (E,E)-9,ll-tetradecadienyl acetate (E,E-9,ll-14:OAc, gift from Shin Etsu Chemical Co. Ltd, Tokyo, Japan; approximately 94% isomerically pure) in a ratio of 100:5 (Bellas et al 1983) dissolved in 25 \x\ of n-pentane. When not in use, the pheromone sources were stored at -15°C.…”
Section: Wind Tunnel Protocolmentioning
confidence: 99%
“…These include insect growth regulators, spinosyns and Bacillus thuringiensis (Bailey et al 1996) In Australia, light brown apple moth has been managed in citrus, grapes and other crop systems using mating disruption (Mo et al 2006). Light brown apple moth pheromone has two key components, both of which must be present for optimal control (Bellas et al 1983;Suckling and Clearwater 1990). Presently, mating disruption is being implemented in some infested areas of California.…”
Section: California Impacts and Controlmentioning
confidence: 99%
“…These same chemicals have also been found in certain Australian tortricine species (Horak et al 1988). There are, however, other species of New Zealand (and Australian, e.g., Epiphyas postvittana; Bellas et al 1983) tortricines that use the ~ 11-tetradecenyl compounds found in the palearctic tortricines (Foster & Dugdale 1988).…”
Section: Introductionmentioning
confidence: 99%